Deferoxamine Counteracts Cisplatin Resistance in A549 Lung Adenocarcinoma Cells by Increasing Vulnerability to Glutamine Deprivation-Induced Cell Death - Liu, Wen-Jun; Pan, Peng-yu; Sun, Ye; Wang, Jian-bo; Zhou, Huan; Xie, Xin; Duan, Zhi-yuan; Dong, Han-yu; Chen, Wen-na; Zhang, Li-de; Wang, Chun (Frontiers in Oncology, 2022)
Glutamine, like glucose, is a major nutrient consumed by cancer cells, yet these cells undergo glutamine starvation in the cores of tumors, forcing them to evolve adaptive metabolic responses. Pharmacologically targeting glutamine metabolism or withdrawal has been exploited for therapeutic purposes, but does not always induce cancer cell death. The mechanism by which cancer cells adapt to resist glutamine starvation in cisplatin-resistant non-small-cell lung cancer (NSCLC) also remains uncertain. Here, we report the potential metabolic vulnerabilities of A549/DDP (drug-resistant human lung adenocarcinoma cell lines) cells, which were more easily killed by the iron chelator deferoxamine (DFO) during glutamine deprivation than their parental cisplatin-sensitive A549 cells. We demonstrate that phenotype resistance to cisplatin is accompanied by adaptive responses during glutamine deprivation partly via higher levels of autophagic activity and apoptosis resistance characteristics. Moreover, this adaptation could be explained by sustained glucose instead of glutamine-dominant complex II-dependent oxidative phosphorylation (OXPHOS). Further investigation revealed that cisplatin-resistant cells sustain OXPHOS partly via iron metabolism reprogramming during glutamine deprivation. This reprogramming might be responsible for mitochondrial iron-sulfur [Fe-S] cluster biogenesis, which has become an “Achilles’ heel,” rendering cancer cells vulnerable to DFO-induced autophagic cell death and apoptosis through c-Jun N-terminal kinase (JNK) signaling. Finally, in vivo studies using xenograft mouse models also confirmed the growth-slowing effect of DFO. In summary, we have elucidated the adaptive responses of cisplatin-resistant NSCLC cells, which balanced stability and plasticity to overcome metabolic reprogramming and permitted them to survive under stress induced by chemotherapy or glutamine starvation. In addition, for the first time, we show that suppressing the growth of cisplatin-resistant NSCLC cells via iron chelator-induced autophagic cell death and apoptosis was possible with DFO treatment. These findings provide a solid basis for targeting mitochondria iron metabolism in cisplatin-resistant NSCLC for therapeutic purposes, and it is plausible to consider that DFO facilitates in the improvement of treatment responses in cisplatin-resistant NSCLC patients.